Effective communication in Audits: A linguistic Perspective - Rasyki, Adrian; Lumban Gaol, Lasando (Universitas Medan Area, 2025)
This study investigates the dynamics of auditor-client communication to establish a balance between technical and non-technical language, communication skills, and satisfaction levels. The research adopts a quantitative analysis in combination to explore how these factors impact communication effectiveness. The study's respondents are 60 auditors, including expert auditors from the BPKP Indonesian Financial and Development Supervisory Agency and P2UPD auditors from the Ministry of Home Affairs, who were chosen for their relevant expertise. The study used a structured questionnaire to examine the frequency and context of technical and non-technical language usage, communication skills, and satisfaction levels. Data were analyzed using multiple linear regression, a statistical method to assess how independent variables influence communication outcomes. Technical language, such as